Spatial analysis of the Zarbatia Reserve in Wasit Governorate using Geographic Information Systems (GIS - Wasan Kareem Ferman; Dr. Dhia AL Deen Abdul –Hussain Uaid (Journal of College of Education, 2024)
A natural reserve is a geographical area with a specific area allocated to the preservation of renewable environmental resources and the application of good systems for their exploitation. A specific body supervises it. These areas are characterized by the fact that they may contain plants or animals threatened with extinction, which necessitates their protection from human encroachment and pollution. A nature reserve can also be known as a wildlife reserve or a terrestrial and aquatic ecological biosphere reserve. Reserves are considered a specific area on land that the state protects and prevents hunting in, and this is through certain laws imposed by the state. Natural reserves are important matters that must be known more broadly (). Zurbatieh Reserve is located in Zurbatieh district, administratively affiliated with Badra District, within Wasit Governorate. The region is characterized by natural diversity and plant and animal diversity due to the natural biological and environmental diversity it contains
Keywords: Geographic information systems - spatial analysis - natural reserves - spatial suitability